1998
DOI: 10.1007/s001340050710
|View full text |Cite|
|
Sign up to set email alerts
|

Hemodynamic profile in severe ARDS: results of the European Collaborative ARDS Study

Abstract: In addition to the cause of ARDS and the early time-course of lung function, a high systolic PAP and a low diastolic SAP were strong independent indicators of survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
91
1
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(104 citation statements)
references
References 31 publications
8
91
1
4
Order By: Relevance
“…This suggests that the initial trigger negatively influences further organ dysfunction and final outcome. One paediatric study on AHRF and multiple adult studies showed that underlying diseases, such as cerebral dysfunction and immune disorders, have a greater impact on outcome than respiratory failure alone [7,18,[22][23][24][25][26][27][28]. These findings suggest that ALI may be more a symptom than a limiting disease.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the initial trigger negatively influences further organ dysfunction and final outcome. One paediatric study on AHRF and multiple adult studies showed that underlying diseases, such as cerebral dysfunction and immune disorders, have a greater impact on outcome than respiratory failure alone [7,18,[22][23][24][25][26][27][28]. These findings suggest that ALI may be more a symptom than a limiting disease.…”
Section: Discussionmentioning
confidence: 99%
“…38 Traditionally, pulmonary hypertension in the course of ARDS was considered a predictor of poor outcome. 67 However, in the era of lung-protective ventilation using low V T , elevated systolic pulmonary artery pressure early in the course of ARDS is not necessarily predictive of poor outcome, although a persistently large dead space in early ARDS remains associated with increased mortality and fewer ventilator-free days. 68 Several studies have demonstrated this association.…”
Section: Prognostic Value Of Dead-space Measurementmentioning
confidence: 99%
“…Mortality rates for ARDS have decreased over time but still remain around 40%, in large part a result of the hemodynamic complications of this syndrome [3]. ARDS has various etiologies and early diagnosis and intervention are key to improving outcomes [4].…”
Section: Introductionmentioning
confidence: 99%